The battle for Algeria sovereignty, health care, and humanitarianism - Johnson, Jennifer 1981- (Pennsylvania studies in human rights, 2016)
In The Battle for Algeria Jennifer Johnson reinterprets one of the most violent wars of decolonization: the Algerian War (1954-1962). Johnson argues that the conflict was about who - France or the National Liberation Front (FLN)-would exercise sovereignty of Algeria. The fight between the two sides was not simply a military affair; it also involved diverse and competing claims about who was positioned to better care for the Algerian people's health and welfare. Johnson focuses on French and Algerian efforts to engage one another off the physical battlefield and highlights the social dimensions of the FLN's winning strategy, which targeted the local and international arenas. Relying on Algerian sources, which make clear the centrality of health and humanitarianism to the nationalists' war effort, Johnson shows how the FLN leadership constructed national health care institutions that provided critical care for the population and functioned as a protostate. Moreover, Johnson demonstrates how the FLN's representatives used postwar rhetoric about rights and national self-determination to legitimize their claims, which led to international recognition of Algerian sovereignty. By examining the local context of the war as well as its international dimensions, Johnson deprovincializes North Africa and proposes a new way to analyze how newly independent countries and nationalist movements engage with the international order. The Algerian case exposed the hypocrisy of selectively applying universal discourse and provided a blueprint for claim-making that nonstate actors and anticolonial leaders throughout the Third World emulated. Consequently, The Battle for Algeria explains the FLN's broad appeal and offers new directions for studying nationalism, decolonization, human rights, public health movements, and concepts of sovereignty